Dimensionen des Erhabenen bei Adalbert Stifter. - Häge, Elisabeth (Studien zur deutschen Literatur., 2017)
The series Studien zur deutschen Literatur (Studies in German Literature) presents outstanding analyses of German-speaking literature from the early modern period to the present day. It particularly embraces comparative, cultural and historical-epistemological questions and serves as a tradition-steeped forum for innovative literary research.